Revision and phylogeny of the genus Balgus Fleutiaux, 1920 (Coleoptera, Elateridae, Thylacosterninae) - Barbosa, Felipe Francisco (Zootaxa, 2016)
The genus Balgus Fleutiaux 1920 was currently comprised of nine species and can be easily distinguished from other Thylacosterninae by the presence of tubercles on the pronotal disk. In this paper a taxonomic revision and a reconstruction of the phylogeny of the genus were performed. Morphological data were analyzed using maximum parsimony (MP) and by Bayesian inference (BI). For BI the Mkv model was used. The genus Balgus and eight of the nine species were redescribed. The subspecies B. schnusei cayennensis Chassain, 2003 was considered a synonym of B. schnusei (Heller, 1914), and the genus was considered monophyletic. An identification key to all species of the genus was generated.